2011
DOI: 10.1016/j.tripleo.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of TGIF1 homeobox gene in oral squamous cell carcinoma according to histologic grading

Abstract: TGIF1 gain or loss of function might possibly play a role in oral cancer cell differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…The analysis of the TGIF1 protein showed that there was a statistically significant difference between the nuclear and cytoplasmic expression when comparing OSCC and NT samples. In line with Matizonkas et al (2011), 14 we agree that TGIF1 cytoplasmic immunolocalization implies that some isoforms could develop additional functions other than transcription. Furthermore, Lo et al (2001) 29 revealed that the mitogenactivated protein kinase transducing pathway can phosphorylate TGIF1, prolonging its half-life and consequently raising its protein level, which could also justify the higher levels of TGIF1 protein in the cytoplasmic compartment of OSCC cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The analysis of the TGIF1 protein showed that there was a statistically significant difference between the nuclear and cytoplasmic expression when comparing OSCC and NT samples. In line with Matizonkas et al (2011), 14 we agree that TGIF1 cytoplasmic immunolocalization implies that some isoforms could develop additional functions other than transcription. Furthermore, Lo et al (2001) 29 revealed that the mitogenactivated protein kinase transducing pathway can phosphorylate TGIF1, prolonging its half-life and consequently raising its protein level, which could also justify the higher levels of TGIF1 protein in the cytoplasmic compartment of OSCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…A previous in situ hybridization study showed that TGIF1 transcripts had a signal that was frequently intense in NT, and generally weak in OSCC, 14 suggesting that TGIF1 expression is higher in NT compared with OSCC. Conversely, by using RT-qPCR, we found no differences regarding TGIF1 expression in OSCC when compared with NT, although an imbalance of specific splicing variants (TGIF1v2, TGIF1v5, and TGIF1v8) was found, which suggests that alternative splicing of TGIF1 may be deregulated in OSCC.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been reported that TGIF is involved in at least three signaling pathways, including retinoic acid (RA) ( 6 ), transforming growth factor β (TGF-β) ( 8 ), and wnt/β-catenin signaling pathways ( 9 ). A number of studies have reported that TGIF plays an important role in the initiation, development, and progression of breast cancer ( 9 ), lung cancer ( 10 12 ), hepatocellular carcinoma ( 13 , 14 ), upper urinary tract urothelial carcinoma ( 15 , 16 ), leukemia ( 17 19 ), and oral squamous cell carcinoma ( 20 , 21 ). Nakakuki et al reported that frequent amplifications of TGIF were observed in esophageal squamous cell carcinoma (ESCC) ( 22 ), which suggests that TGIF might be associated with esophageal tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…na progressão e metástase do carcinoma epidermóide bucal.A análise de transcritos e proteína do gene homeobox TGIF1 foi recentemente avaliada porMatizonkas et al (2011). Foi demonstrado que este gene encontra-se altamente expresso no tecido oral normal, sendo fracamente expresso em amostras de carcinoma epidermóide bucal.…”
unclassified